Penegakan hak asasi manusia dalam menjamin kebebasan berpendapat di ruang siber: Perubahan cara pandang hukum di Indonesia - Ramadhani, Andrea Laudya (Maliki Interdisciplinary Journal, 2026)
This study aims to analyze the importance of upholding human rights in ensuring freedom of expression in an increasingly restricted digital space. In the era of digital technology development, the protection of citizens’ rights often clashes with digital security policies that employ rules subject to varying interpretations. Using a research methodology grounded in legal analysis and applicable regulations, this study examines the impact of digital security measures on the shrinking of democratic space and the emergence of public fear regarding the expression of opinions in digital media. The research findings indicate that a law enforcement approach that prioritizes punishment creates legal uncertainty and adversely affects public freedom in the digital realm. The study’s conclusion underscores the need for a shift in the law enforcement approach—from a repressive stance to one that prioritizes the protection of citizens’ rights. Consequently, updates to digital regulations are necessary to align with principles of justice and legal certainty, thereby fostering a healthy and equitable digital democratic space.